SUPERVISI ADMINISTRASI PERENCANAAN PEMBELAJARAN SEBAGAI UPAYA PENINGKATAN KOMPETENSI PEDAGOGIK GURU DALAM MENEJEMEN KELAS DI SMP NEGERI 2 LELEA KABUPATEN INDRAMAYU - Pramono, Tutus (MADINASIKA, 2022)
This study aims to find out the right steps in carrying out class administration supervision so as to be able to improve the pedagogical competence of teachers, especially in classroom management which will ultimately affect the improvement of the quality of education. The study was conducted with two cycles. Each cycle has different planning, execution, observation, and reflection. Research subjects of teachers of SMP Negeri 2 Leua, Indramayu Regency Academic Year 2020/2021. Teachers as objects as well as subjects in the treatment of class administration supervision activities. Data collection techniques through administrative supervision of learning planning with document analysis and classroom observation, to record important matters and events related to research. Data analysis techniques that guide data processing using percentages (%) of achievements with a constant of 100. Furthermore, to look at the interpertation by using the score interpertation criteria to reinforce the interpretation in conclusions as follows: 80%-100% (very good), 66%-79% (good), 56%-65% (sufficient), and 40%-55% (less). The results showed that the teacher's ability in the implementation of learning has increased by percentage at each stage, from the results of precyclical, cycle I, cycle II, the teacher's ability to manage classes has increased by percentage at each stage from the new precyclical reaching 55.00% (less), in cycle I reaching 61.50% (enough), and cycle II reaching 72.25% (good).